Social art cinema of the 1990s: commodifying the concept of British National Cinema - Jeongmee, Kim (2003)
This study explores the ways in which "social art cinema" has been constructed as a form of national cinema in the context of the 1990s. It discusses how particular institutional issues of the period affected signification revolving around the genre and, consequently, how that affected the concept of national cinema. This research draws upon a range of agendas relating to financial and distribution structures, promotional activities and multi-media consumption that were involved in encouraging the proliferation of social art cinema. This study contends that the success of social art cinema as a generic style was a key factor in constructing an idea of British cinema as a cultural entity. By examining how the institutional elements created this idea, I discuss how social art cinema was positioned as a national cinema in the market place through such elements. The primary objective of this study is therefore to make a contribution towards the growing body of scholarly work that considers the role played by the idea of national cinema in the very commercial environment of the contemporary film business where expressions of national specificity can often seen indistinct. The study also presents evidence for the need to consider contextual aspects when discussing the idea of national cinema. Thus, by examining the commercial aspects of national cinema, I demonstrate that national cinema should not only be defined by accounts of socio-political engagement, but should encompass institutional agendas as well.